REORGANIZATION OF REGIONAL ENVIRONMENTAL INSTITUTION - Bagus Oktafian Abrianto; Suparto Wijoyo (Yuridika, 2017)
Nowadays, The Institutional of environmental in regional experinced many changes, its cause of stipulated of Law No. 23 of 2014 on Local Government and Government Act No. 18 of 2016 on Local Government Organization. Rule about central government authority and local government authority on environment aspect that ruled by Act No. 32 of 2009 on Protection and Management of Environment must be adjusted with Act No. 23 of 2014 on Local Government and Government Act No. 18 of 2016 on Local Government Organization. This research analyze about institutional harmonization on statute approaches. It is expected that this research give a knowledge of affairs which central government authority, province government authority, and district/regency government authority clearly especially on environment aspect. The minister of environment and forestry in order to implementing coordinative function, should be obliged to synchronize working program of environment institution between local and central government for making integrated environment management (policy) approaches.